PENGARUH TRANSGLOBAL LEADERSHIP DAN WORK ENGAGEMENT TERHADAP KINERJA KARYAWAN - Ina Syarifah (P3I Politeknik Negeri Madiun, 2021)
A leader must think of himself as a citizen of an open world. Transglobal leadership is needed because of transglobal trade and global technology integration. Future managers must understand how to handle global production, marketing, and sales to achieve a competitive advantage. Based on this, it is necessary to have support from the company to improve employee performance so that organizational goals can be achieved properly. Employee behavior in improving their performance is a response to the support provided by the company through transglobal leadership and can then encourage work involvement. The purpose of this study is to determine the factors that can influence transglobal leadership and work involvement in improving employee performance and to determine the factors that most influence the performance of SME Handicraft employees in Malang City. This study uses an explanatory with a quantitative approach. The primary data used in this study were collected by distributing questionnaires to 60 UKM Crafts employees in Malang City via an online method using Google.form. The sampling technique in this study used the proportional random sampling method. Determine the number of samples using the Roscoe formula. The results showed that transglobal leadership has a significant influence on employee performance.